Synthesis and Preliminary Screening of Carbohydrazides and Hydrazones of Pyrrole Derivatives as Potential Tuberculostatics - Bijev, Atanas (Arzneimittelforschung, 2006)
Five carbohydrazides and 19 hydrazones of carboxylic acids of pyrrole were synthesized as new structural analogs of known tuberculostatics, such as isoniazid (CAS 54-85-3) and its popular hydrazones. The preliminary screening against Mycobacterium tuberculosis H37Rv (ATCC 27294) at 6.25 µg/mL in 12B medium using a broth microdilution assay, the Microplate Alamar Blue Assay (MABA) registered higher inhibitory activity within the hydrazones series (up to 68 % inhibition) compared with that of the carbohydrazides (0–34 %).No simple relationship between the activity of a particular hydrazone and that of the parent carbohydrazide, or correlations with the structural features introduced by the carbonyl partner could be observed. So both most active hydrazones diethyl 5-(2-[(2,4-dimethyl-1H-3-pyrrolyl)carbonyl]hydrazonomethyl)-3-methyl-1H-2,4-pyrroledicarboxylate (22, 68 % inhibition) and ethyl 5-(4-chlorophenyl)-2-methyl-1-(2-2-[1-(5-nitro-2-furyl)methylidene]hydrazino-2-oxoethyl)-1H-3-pyrrolecarboxylate (32, 55 %) originated from inactive carbohydrazides (1, 0 % and 7, 10 % respectively); ethyl 1-(2-2-[1-(3-ethoxy-4-hydroxyphenyl) methylidene] hydrazino-2-oxoethyl)-2-methyl-5-(4-nitrophenyl)-1H-3-pyrrolecarboxylate (30) showed 0 % inhibition, although derived from a hydrazide with 34 % activity. The condensation of six carbohydrazides with the same carbonyl reagent 5-nitrofurfural yielded hydrazones whose activity covered the wide range of 0–55 % inhibition.
Keywords: Carbohydrazides, synthesis, tuberculostatic activity; CAS 54-85-3; Hydrazones, synthesis, tuberculostatic activity; Isoniazid, pyrrole analogs; Tuberculostatics